Temporarily Aligned Interest: Cooperation Between Turkey and The United States in The Syrian Civil War - Arkan, Muhammad (Jurnal Diplomasi Pertahanan, 2021)
The Syrian Civil War, starting from 2011 and still ongoing, is one of the largest conflicts in the region which highly affected the overall stability of the region and has involved several parties. With multiple factions fighting each other inside the territory of Syria and sometimes clashing through the border regions of neighbouring countries, it is inevitable for Syria’s neighbours such as Turkey to react. With the decreasing regional stability of the Middle East, a region which has caught the interests of many other powers such as The United States due to its abundance of resources (primarily oil), western nations too eventually take action towards the civil war. Condenming the Syrian Government under President Bashar Al Assad for alleged human rights violations towards their own citizens, the United States along with Turkey sided with anti-government rebellions and actively supported them by supplying weapons and munitions, along with providing military training. However, despite having mutual interest on supporting anti-government rebels and later countering ISIS offensives, the Interests of Turkey and US are not always in-line with each other.